Layanan Informasi Berbasis Pohon Karier untuk Meningkatkan Pemahaman Perencanaan Karier Siswa - Sukma Gita Lestari; Ramtia Darma Putri; Nurlela (Syifaul Qulub: Jurnal Bimbingan dan Konseling Islam, 2021)
Problems that are often encountered in career planning are students who choose the wrong career because they are forced to follow the wishes of their parents so that careers that are in accordance with the child's wishes, talents, and abilities are ignored. The intervention of parents who tend to dominate their desires in children's studies is considered the right decision, while children are considered still unable to determine attitudes and make decisions to plan their careers. Some of the difficulties that arise during the job search process often occur because individuals do not have a clear career planning direction. In addition, job providers are also more selective in finding and selecting prospective employees. The purpose of this study is to determine whether the use of career tree-based information services can improve students' understanding of career planning or not. This study uses quantitative research with a Quasi-Experimental design experimental research method. The Quasi-Experimental form used in this study is the Pretest Posttest Group Design with a sample of 35 people. The instrument used in this study used a Likert scale model. The results showed that career tree-based information services can improve students' understanding of career plans. Students can understand clearly and with a strong passion to determine their own career by referring to various information obtained through the career